Toleranz im Zeitalter des Aufgeklärten Absolutismus. Soziale und ökonomische Auswirkungen des Toleranzpatents 1782 für die jüdische Bevölkerung in Wien und Niederösterreich - Michaela Seewald (Historia.scribere)
The purpose of this thesis is to highlight the “tolerance patent” of 1782 and the impacts it had on the Jewish population within the centre of Habsburg monarchy, namely Vienna and Lower Austria. The paper is divided into two sections. The first chapter gives an overview of political conditions and the process of enactment. The second part concentrates on the various effects the patent had, especially economic, religious, social and cultural aspects. The paper concludes with an overview of the results and my conclusions about the importance of the development on religious liberty.